Nanodevices Based on Quantum Mechanics and Classsical Electrodynamics as Vascular Endothelial Growth Blockers to Detain Angiogenesis - Nieto-Chaupis, Huber (2020)
The processes of angiogenesis have among their initial phases the processes such as the vascular endothelial growth (VEG) in order to guarantee the consistent sprouting and splitting of new blood vessels whose main purpose is the fueling of tumor. In this paper we develop a technique entirely based on Quantum Mechanics and Classical Electrodynamics to tackle down scenarios of anomalous growth of vessels. In conjunction to Classical Electrodynamics, we use Quantum Mechanics calculations to a more accurate prediction of the location and the subsequent detaining of anomalous growth of vessels that give rises to angiogenesis. For nanodevices whose size is of order of 10nm, the probability to identify a tube from VEG might be of order of 16%.